2019
DOI: 10.4103/jmas.jmas_130_18
|View full text |Cite
|
Sign up to set email alerts
|

Exploring minimally invasive options: Laparoscopic transabdominal levator transection for low rectal cancers

Abstract: Extralevator abdominoperineal excision (ELAPE) of the rectum offers wider circumferential margin and decreased rate of intraoperative tumour perforation. However, the need to change the position of the patient in between abdominal and perineal stages of the procedure and extended perineal resection result in increased morbidity and operative time. Evolving technique of laparoscopic transabdominal controlled division of levator ani muscles under direct vision could address these issues while providing all benef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Since the implementation of LDAPR surgery in 2017, our team has found that individualised excision of the levator ani muscle under laparoscopic direct vision and avoiding the removal of the levator ani muscle through the perineal approach can reduce the damage to the nerve collateral caused by poor visual field. [ 22 ] Maximising the protection of the pelvic autonomic nerves related to urination and sexual function is also important in reducing the incidence of ITP and perineal complications. In addition, the confluent plane of the abdomen and perineum is reduced to the ischiorectal fossa fat, and the perineal surgery group can easily reach the same level as the abdominal group.…”
Section: Discussionmentioning
confidence: 99%
“…Since the implementation of LDAPR surgery in 2017, our team has found that individualised excision of the levator ani muscle under laparoscopic direct vision and avoiding the removal of the levator ani muscle through the perineal approach can reduce the damage to the nerve collateral caused by poor visual field. [ 22 ] Maximising the protection of the pelvic autonomic nerves related to urination and sexual function is also important in reducing the incidence of ITP and perineal complications. In addition, the confluent plane of the abdomen and perineum is reduced to the ischiorectal fossa fat, and the perineal surgery group can easily reach the same level as the abdominal group.…”
Section: Discussionmentioning
confidence: 99%
“…We had shown that as the experience of surgical team improved, there was a trend towards selecting difficult cases and performing complex laparoscopic colorectal resections. [ 18 19 ] In a study comprising 170 laparoscopic anterior resections Palanivelu C et al . concluded that laparoscopic anterior resections could be done for rectal tumours at all levels, which would allow sphincter preservation and maintain oncological safety.…”
Section: Discussionmentioning
confidence: 99%
“…These include airway complications (endotracheal tube displacement), oropharyngeal swelling, acute glaucoma, optical compartment syndrome, cardiovascular compromise and neurological injuries ( 22 ). These problems with ELAPE were acknowledged and a subsequent modification of the ELAPE technique, termed laparoscopic transabdominal ELAPE, removed the need for position change to a prone position and so reduced patient morbidity and operating times ( 23 ).…”
Section: Drawbacks Of the New Techniquementioning
confidence: 99%